An Influence Study of Face Length Effect on Floor Stability under Water-Rock Coupling Action. (10th March 2021) - Fu, Baojie; Wang, Bo
Abstract : The Taiyuan Formation limestone aquifer and Ordovician limestone aquifer are widely distributed in the coal seam floor of coal measures in North China; the water hazard safety problem of the stope floor under the influence of mining is very prominent. The risk of the water inrush from the coal seam floor is closely related to the degree of full exploitation, so it is necessary to study the stability of the stope floor under aquifer conditions, especially the influence of the working face length effect on floor stability. Through numerical simulation of water-rock coupling action, the mine pressure behaviors of the water-resisting floor under different face lengths were analyzed based on the measured formation permeability coefficient. The Fish program was used to adjust rocks entering the plastic failure state into a strain softening model to investigate the influence of the face length effect, the damage degree of the water-resisting floor, and the morphology and deformation bearing capacity of the failure zone. The results show the following: (1) the face length effect is one of the main influence factors of the failure mode and failure degree of surrounding rocks in the stope; (2) as the face length increases, the obvious pressure relief zone of surrounding rocks presents a staged change, and the obvious pressure relief zone at the seam roof and floor is in an obvious "reverse saddle shape"; (3) the closer to the seam floor, the more remarkable the rock softening characteristic because of the compaction action of gangues caving from the roof; and (4) the rock mass close to the seam floor undergoes local tensile failure, and the water-resisting floor near the coal wall at two sides mainly bears compaction-shear action, leading to compression-shear failure of the rock mass at the floor and formation of water-conducting fractures. The study results can provide a reference for taking precautionary measures of safety mining above a confined aquifer.